Cooperative environmental engineering via biofilm formation can stabilize consumer-resource systems - Bryan K. Lynn; Patrick De Leenheer; Benjamin D. Dalziel (PLoS ONE, 2025)
Cooperation can stabilize consumer-resource dynamics, preventing over-exploitation driven by individual self-interest. The maintenance of cooperation in such systems is often attributed to individual-level behaviors, such as punishment of defectors, however, an alternate and under-explored path to stability involves environmental engineering by cooperative consumers, who may modify the environment to favor cooperators. Microbial biofilms are an important instance of cooperative resource use involving environmental modification. Here, we demonstrate that biofilms can stabilize cooperative populations against cheating by giving preferential access of resources to cooperators, ensuring positive growth rates for cooperators when rare. We show that collective environmental modification offers pathways to stability across a broad parameter space, encompassing a range of rates for physiological processes, social behaviors, and environmental interactions. Including cooperative environmental modification in models of consumer-resource dynamics opens novel directions for understanding and managing ecological and evolutionary dynamics in social systems.